VOLUNTEER MOVEMENT IN UKRAINE AS AN ELEMENT OF THE NATIONAL SECURITY SYSTEM: MODERNITY AND PROSPECTS - Євгеній СЛЮСАР (Епістемологічні дослідження у філософії, соціальних і політичних науках)
The article examines the phenomenon of the domestic volunteer movement as an important element of the system of national security and stability in war conditions. The main directions of volunteer activity and the interaction of volunteer organizations with state authorities are outlined. The emphasis is on the uniqueness of Ukrainian volunteering as a phenomenon of civil society cohesion and mobilization of the social activity resource of certain population groups in response to an external threat. The features of the periods of formation and functioning of the volunteering institute in the country and the main directions of work since 2014 are considered. It has been emphasized that the current period of volunteer organizations in the country can be characterized as a creative development of the experience already acquired in 2014-2017 during the anti-terrorist operation in Eastern Ukraine and the development of competencies of its participants in normalizing cooperation between volunteers and the authorities. The process of transforming the volunteer movement into a component of the national security system was facilitated by the adoption by the Verkhovna Rada of Ukraine of the Military Doctrine of Ukraine (2015) and a number of laws. These are the Law of Ukraine “On National Security of Ukraine” (2015), the Law of Ukraine “On Amendments to the Law “On Volunteer Activities” (2015) which stabilized the legal relations of volunteers with the state and contributed to the further reassessment of the role of volunteers in strengthening national security. It has been also emphasized that the volunteering stage since 2022 has combined the experience of previous years with modern technologies and international support, creating a qualitatively new level of efficiency in providing the needs of society in the conditions of escalating hostilities. The priority areas of work of volunteer organizations during military operations, starting in 2022, have been revealed. They include active assistance to units of the Armed Forces of Ukraine that are directly on the “line of fire”. Volunteers actively provide the military with the necessary equipment, including ammunition, body armor, helmets, tactical equipment, means of communication and personal protection. As for the population of the “front-line” territories, this work covers a wide range of activities aimed at meeting basic human needs – food, medicine, clothing, household repairs. Volunteers provide internally displaced persons with food, clothing, footwear, medicines, hygiene products, as well as warm things for the winter period, etc. The challenges to the activities of volunteer organizations have been analyzed, the main of which are the uneven distribution of resources, insufficient social protection of participants in the structures, lack of funding, and shortcomings in integration into national security policy programs.